Implementation of Elective Subject Selection Program in the Merdeka Curriculum - Lestari, Risti Dwi; Rusman, Rusman; Adeoye, Moses Adeleke (Lembaran Ilmu Kependidikan, 2024)
Referring to several evaluation results of the 2013 Curriculum, the learning load is too large, it limits schools in designing education according to school conditions, and the existence of a reading system still causes students to have a fixed mindset. The government's response was to implement the Merdeka Curriculum through an elective subject selection program. This research aims to describe the implementation of the elective subject selection program. This research was conducted using a qualitative descriptive approach, with data collection techniques through interviews. The research subjects were three guidance counseling teachers from SMA Negeri 19 Bandung. The results show that the elective subject selection program has been implemented at SMA Negeri 19 Bandung, as evidenced by the program scheme created by the school with the elective subject selection program guide issued by the Minister of Education, Culture, Research, and Technology. The activities carried out by the school are quite diverse,  collaborating with internal schools but also external parties to implement this program a success. However, schools still have to face challenges such as the need to continue to carry out updates with each new generation by adjusting the condition of school infrastructure and the availability of teaching teachers so that the spirit of the elective subject selection program continues to be created, namely creating independence for each student. It is hoped that the research results obtained will be able to become a reference for other schools in preparing and implementing elective subject selection program schemes that suit the conditions of their respective schools.